1998
DOI: 10.1056/nejm199802263380901
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Finasteride on the Risk of Acute Urinary Retention and the Need for Surgical Treatment among Men with Benign Prostatic Hyperplasia

Abstract: Among men with symptoms of urinary obstruction and prostatic enlargement, treatment with finasteride for four years reduces symptoms and prostate volume, increases the urinary flow rate, and reduces the risk of surgery and acute urinary retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
297
2
9

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,028 publications
(314 citation statements)
references
References 24 publications
6
297
2
9
Order By: Relevance
“…27 The clinical, chemical, and volumetric observations made in the present group of long-term finasteride responders are consistent with previous reports. [1][2][3][4][5] After 6 months of treatment, prostate volume decreases by approximately 18% to 20%; serum levels of DHT and PSA decrease by approximately 70% and 50%, respectively; voiding symptoms and flow rates are improved; and the new levels are maintained for years thereafter. Thus, the present group of patients, although highly selected (see Material and Methods, Patients), appears to be representative of the thousands of men studied in other clinical trials.…”
Section: Huggins and Stevensmentioning
confidence: 99%
See 2 more Smart Citations
“…27 The clinical, chemical, and volumetric observations made in the present group of long-term finasteride responders are consistent with previous reports. [1][2][3][4][5] After 6 months of treatment, prostate volume decreases by approximately 18% to 20%; serum levels of DHT and PSA decrease by approximately 70% and 50%, respectively; voiding symptoms and flow rates are improved; and the new levels are maintained for years thereafter. Thus, the present group of patients, although highly selected (see Material and Methods, Patients), appears to be representative of the thousands of men studied in other clinical trials.…”
Section: Huggins and Stevensmentioning
confidence: 99%
“…1 Moreover, the treated men also experienced a 55% reduction in risk of surgical intervention and a 57% reduction in risk of acute urinary retention compared with the untreated men. 1 However, prostatic tissue changes, which may explain the clinical effects of finasteride, have only been systematically evaluated for up to 6 months of treatment. 6,7 Long-term tissue effects might have important implications regarding the mechanism of action of the drug.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The results of the USA PLESS study, 30 the largest and longest BPH study ever completed, was ®rst reported by Dr J McConnell at the SIU meeting in Montreal in September 1997. This landmark study con®rmed the hypothesis generated by the Endpoint Analysis.…”
Section: Does Medical Therapy Change the Incidence Of Bph Complications?mentioning
confidence: 99%
“…4 Recently, a number of studies reported that early administration of a 5-alpha reductase inhibitor (Proscar) to BPH patients is able to reduce the chance of prostate surgery by around 50%. 5 However, owing to the lack of reliable biomarkers for early detection, majority of BPH patients are presented at late stage, which may not be reverted even after TURP. 6 Therefore, early detection as well as prevention of the progression of this disease is essential for the successful treatment of BPH.…”
Section: Introductionmentioning
confidence: 99%